Peningkatan Kapasitas (Capacity Building) Aparatur Pemerintahan Desa Kota Kapur Kabupaten Bangka - Darus Altin (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
One indicator of the success of a village is the ability of its village apparatus to manage development. Kota Kapur Village is a village that is still considered to have a lack of development touch, especially in increasing the capacity of the village apparatus. The number of Kota Kapur Village officials totaling 20 people is part of the duties and functions of each in the Village Government. Some are in charge of running the wheels of administration, finance, organization and so on. Each of them certainly requires an increase in expertise in their field. For this reason, it is necessary to touch on capacity building in certain fields such as; skills in computers, accounting, administration and organizational management, village regulations and making maps of the village area to prepare Kota Kapur Village to become a Tourism Ready Village. The achievements of KKN activities in Kota Kapur Village are the achievement of Village Apparatus who have the ability to operate computers, are able to manage Village Accounting and Finance, are able to manage administration, are able to create and design Village Regulations and create Village Maps that are accurate and academically accountable. The achievements of KKN activities in Kota Kapur Village are the achievement of Village Apparatus who have the ability to operate computers, are able to manage Village Accounting and Finance, are able to manage administration, are able to make and draft Village Regulations and create Village Maps that are accurate and academically accountable. From this KKN activity, it is hoped that the Kota Kapur Village apparatus will optimize and maximize the potential of human resources in managing and compiling structured and systematic financial reports by using existing facilities and infrastructure in supporting financial performance, paying more attention to the completeness of financial data for the preparation of bookkeeping reports in accordance with predetermined standards. In the applied civil sector so that it clarifies the boundaries between villages and improves village spatial planning, the achievement of village administrative governance in order to achieve an effective and efficient village government system, and it is hoped that the Bangka Regency Government in collaboration with the Kota kapur village government will pay more attention to the Kota kapur village regarding the historical sites located in the village. Where it is one of the most valuable assets that is not owned by all regions in Bangka Belitung.